Opportunities and Challenges for Regional Coordination of Infectious Disease Control; Comment on "Operationalising Regional Cooperation for Infectious Disease Control: A Scoping Review of Regional Disease Control Bodies and Networks" - Claire Standley; Erin Sorrell (Kerman University of Medical Sciences, 2022)
This commentary cites a scoping review by Durrance-Bagale et al on how regional bodies have approached infectious disease control to determine if those lessons could be applied to assist the Association of Southeast Asian Nations (ASEAN). The author's work is timely and highlights the importance of recognizing and understanding regional context, governance and operational structures to then design effective regional networks. Most factors highlighted as enablers and constraints are quite expected, including stakeholder mapping, a clear mission space with goals and objectives, outreach and advocacy to receive buy-in, political will and sustainable funding. We suggest below that there is an opportunity for further systematic and operational research of enablers and constraints for regional infectious disease control bodies, one that expands on infectious disease control while also continuing to take into account governance, legislative and organizational factors, and strongly emphasizes the development and application of clear metrics to create better measures of impact.